Sales & excellence of Kuehne + Nagel Bangladesh Limited - Khan, A.B.M Atiq Faisal (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.